Circulating liver-specific miR-122 as a novel potential biomarker for diagnosis of cholestatic liver injury. - Huang Shifeng; Wang Danni; Chen Pu; Yang Ping; Cao Ju; Zhang Liping (PLoS ONE, 2013)
BACKGROUND: Circulating microRNA-122 (miR-122) has been increasingly reported to be a potential biomarker for drug-, viral-, alcohol- and chemical-induced liver injury. The present study was initiated to determine the potential of circulating miR-122 as a biomarker for cholestatic liver injury. METHODS: Both bile-duct ligation (BDL) mice and patients with biliary calculi were employed as cholestatic liver injury models, and serum miR-122 level was determined by stem-loop real-time reverse-transcription PCR (SLqRT-PCR). All quantitative PCR values were normalized to those for U6 RNA and calculated with the 2(-△Ct) method. RESULTS: Serum miR-122 increased significantly after BDL-induced cholestatic injury and showed a similar time course to ALT concentrations. Compared with the sham controls, BDL mice had increased serum levels of miR-122 by 24.36±12.86, 423.63±322.89, 4.43±2.02 and 12.23±8.92 folds after 1, 3, 7 and 14 days, respectively. Moreover, serum miR-122 level was substantially higher in patients with biliary calculi than that in the healthy control group. In addition, patients with severe liver injury showed significantly higher levels of serum miR-122 when compared with healthy controls or patients with mild or moderate liver injury. Furthermore, serum miR-122 was found to show significant diagnostic value for biliary calculi by yielding an AUC (the areas under the receiver operating characteristic curve) of 0.931 with 77.4% sensitivity and 96.4% specificity in discriminating biliary calculi from healthy controls. CONCLUSION: Collectively, these data suggest that serum miR-122 has strong potential as a novel, specific and noninvasive biomarker for diagnosis of cholestasis-induced liver injury.